DEVELOPING WORD-CARD GAMES TO IMPROVE ENGLISH WRITING - Limantoro, Singgih Widodo (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Facing the English Language Teaching (ELT) challenges nowadays, the English teachers could facilitate language learning in effective and joyful ways by creating the word-card games for learning English. In this study, the writer would like to investigate whether the word-card games he designed and developed would be the effective strategy to improve students' vocabulary and grammar for writing. There were twenty-one students participating in this classroom action research. It is also essential to know how the English teachers could meet the needs and levels of competence and design the effective word-card games for learning English. It was unique to create four topics of the games, such as Synonyms, Antonyms, Degrees of Comparison, and Making Sentences by using the same cards, to apply pedagogical principles, and also to choose a scorer for each group to help conduct successful games. The word-card games also needed some continuous improvement by trying to play the word-card games with different respondents or players in order to gain necessary feedbacks to improve the shortcomings of the word-card games. In this study, most of his students or respondents gave positive feedbacks of the word-card games for learning English especially for enhancing the joy of learning and strengthening their writing skill.